Kemampuan Literasi Media Sosial pada Peserta Didik Sekolah Menengah Kejuruan di Semarang - Anandha; Pratamanti, Enggar Dhian; Transinata, Tatas (Kajian Bahasa dan Sastra (KABASTRA), 2022)
The personal social media makes people easily upload narration, photos, or videos using their own accounts. Online learning system during the pandemic makes the students having less social interaction that affects their character development. The problem is the lack of language politeness in social media. This can be seen in the improper dictions which found on social media. The purpose of this Community Service Program is to increase the social media literacy skills for the students of Semarang Vocational High School named Sekolah Menengah Kejuruan Perdana Semarang. Having the literacy skills, students would be able to use social media wisely. Discussion and socialization methods had used in this community service. Result of this Community Service Program is the increasing social media knowledge and social media literacy skills of the students of SMK Perdana Semarang.